Case Report: Resolution of complete heart block following vitamin D supplementation in a child with Graves disease - Ilmer, Sofya; Salemi, Parissa (Frontiers in Endocrinology, 2026)
This case report describes an 11-year-old male with Graves disease and pre-existing Mobitz type 1 second-degree atrioventricular (AV) block that progressed to complete heart block (CHB) one month prior to his diagnosis of Graves disease. He presented at age 9 years (January 2023) with weight loss, heat intolerance, and excessive sweating. Laboratory testing revealed: thyroid stimulating hormone (TSH) <0.01 uIU/mL, free thyroxine (FT4) 4.8 ng/dL, total thyroxine (T4) 16.7 µg/dL, and total triiodothyronine (T3) 334 ng/dL. He was treated with methimazole and was biochemically euthyroid within one month of treatment. Despite becoming euthyroid, the CHB persisted. By April of 2023, his cardiologist recommended the implantation of a pacemaker, however the family opted for continued monitoring instead. Following his mother’s research into potential benefits of vitamin D in autoimmune thyroid disease, vitamin D3 supplementation 2500 IU daily was initiated in late October 2023. Three months later, his nighttime bradycardia resolved. A 12-lead ECG in April 2024 confirmed the resolution of CHB to first-degree AV block. No additional medications were used to treat his cardiac condition. Patient remained stable with first-degree heart block while euthyroid on low dose methimazole. He continued vitamin D supplementation at 2000 IU daily. Peak TSH receptor antibody (TSHRab) and thyroid-stimulating immunoglobulin (TSI) values decreased following vitamin D3 initiation. Several proposed mechanisms may explain this observation, including vitamin D’s immunomodulatory effects on Graves disease, its cardioprotective properties, and its potential synergistic effect with methimazole in achieving better thyroid control. This case highlights a potential association between vitamin D supplementation and improved AV block in a pediatric patient with Graves disease, warranting further investigation into vitamin D’s role in managing cardiac manifestations of autoimmune thyroid disease.